2022
DOI: 10.1159/000528586
|View full text |Cite
|
Sign up to set email alerts
|

Inflammatory Bowel Disease Patients’ Preferences for Subcutaneous versus Intravenous Therapies: A Mixed-Methods Study

Abstract: Background Multiple biologics are available to treat inflammatory bowel disease (IBD), which can either be administered subcutaneously (SC) or intravenously (IV). The factors that determine patients’ preferences for SC/IV administration in IBD are largely unknown. This study aims to elucidate how IBD patients trade-off between medications’ route of administration and other medication characteristics, and to understand what drives patients’ preferences. Methods We employed a mixed methods design using data fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 28 publications
(43 reference statements)
0
2
0
Order By: Relevance
“…Van Deen et al found that current and past modes of drug administration were strong predictors of preference. 26 In our cohort, 50 patients (46.3%) had only experience with IV medication, and IV preference at switch was associated with higher risk for discontinuation of SC VDZ. We have previously reported a change in preference at switch to 6-month follow-up favoring SC formulation, suggesting that preference can change when gaining positive experience with the new formulation.…”
Section: Discussionmentioning
confidence: 71%
“…Van Deen et al found that current and past modes of drug administration were strong predictors of preference. 26 In our cohort, 50 patients (46.3%) had only experience with IV medication, and IV preference at switch was associated with higher risk for discontinuation of SC VDZ. We have previously reported a change in preference at switch to 6-month follow-up favoring SC formulation, suggesting that preference can change when gaining positive experience with the new formulation.…”
Section: Discussionmentioning
confidence: 71%
“…Specifically, among patients with experience only with SC administration, 61% preferred SC, while among those with experience only with IV administration, 40% favored SC. For patients with experience with both, 53% expressed a preference for SC administration [ 25 ]. Indeed, in our study, patients with prior SC exposure but no IV history preferred SC treatment every 2 weeks, while those with prior IV exposure but no SC history favored the IV route every 8 weeks.…”
Section: Discussionmentioning
confidence: 99%